Development of In-House ELISA using recombinant LipL32 for Detection of Human Leptospirosis in Indonesia - Sumarningsih, Sumarningsih; Sekarmila, Gita; Mulyadi, Andi; Ahpas, Ahpas; Tarigan, Simson (Jurnal Sain Veteriner, 2024)
Early laboratory confirmation is important for the accurate diagnosis and treatment of patient infected by leptospirosis. However, Microscopic agglutination test (MAT) as the gold standard for detection of human leptospirosis has many limitation and only available in reference laboratories. Therefore, many studies suggested LipL32 protein as a good candidate for development of leptospirosis detection kit because it is highly conserved and produced only in pathogenic Leptospira species. In this study, we aim to investigate the performance of our in-house ELISA using recombinant LipL32 to detect leptospirosis in Indonesia. Fourteen human sera were used in this study and the infection status were determine using MAT. The result showed that nine of eleven MAT positive sera were successfully recognized by LipL32 ELISA. The antibody binding to LipL32 was also confirm by immunoblot. There was one of three MAT negative sera has high OD above 0.5 in ELISA, but it showed negative reaction in immunoblot result. Overall, this study demonstrated that recombinant LipL32 protein can recognized antibody from human leptospirosis and can be used as a universal antigen to detect infection by any serovars of pathogenic leptospira.